Women in leadership positions and firm innovation: Are there differences between countries? - Sara Luisa Nussbaum (Junior Management Science (JUMS), 2024)
The presence of women on corporate boards has attracted significant attention in recent years due to ongoing political discourse concerning initiatives such as gender quotas in managerial and boardroom positions. But how does the proportion of women on corporate boards influence firm innovation? This paper examines this question with reference to the direct and indirect effects of female supervisory board representation. The paper draws on a sample of 60 French firms and is framed in upper echelons theory. In analyzing the proportion of women directors, the paper aims to understand better the relationship between firm innovation and board seats occupied by women. The results suggest that firm innovation is not related to female board representation, which contrasts with empirical evidence that has found a positive relationship for 105 German firms. This deviation from established findings highlights the complexity inherent in understanding the impact of gender diversity on firm-level outcomes and underscores the need for context-specific examinations in this domain.
Keywords: 650; corporate boards; female representation; firm innovation; gender diversity; strategic leadership